RED RICE CREAM HORN WITH THE SUBSTITUTION OF RED RICE FLOUR AS A DESSERT PRODUCT INNOVATION - Minta Harsana, Dian Natasha Anggraeni (Prosiding Pendidikan Teknik Boga Busana, 2020)
The need for flour in Indonesia was increasing because the consumption of Indonesian people towards flour-based food was increased. Pastry was one of popular foods in Indonesia, one of their products were cream horn. All this time pastry products used flour as their main ingredients. To reduce the increasing need of flour and imported wheat in Indonesia, this study used local food ingredients, one of which was red rice flour to substitute the flour. The development of pastry products that use local food ingredients were limited, especially on cream horn. The objective of this study was to find a standard recipe, discover the nutrient content, and to know consumer acceptance of cream horn with red rice substitution. To find the standard recipe, this study used research and development with 4D development model which resulted 15% substitution of red rice flour. Proximate analysis was used to discover the nutrient content which resulted carbohydrate as the most dominant nutrients. Hedonic test was used in this study and resulted red rice cream horn is liked by consumer. Keywords: Red Rice Cream Horn, Red Rice Flour, Proximate Analysis